Implementation of Home Economics Curriculum in Private and Public Secondary Schools in Plateau State, Nigeria - Keswet, Larai A.; John, Yusuf Salome; Margaret, Kazi Mahcit (NIU Journal of Humanities, 2019)
The school is one of the important agents of instruction which diffuses education from one generation to another in order to realize the goals of humanity. One of the objectives of the Nigerian government as well is to instil the right type of value and attitude for the existence of the individual and the society at large.  Thus, the classroom teacher is expected to provide learning experiences through the process of curriculum implementation. This study examines the implementation of home economics curriculum in secondary schools in plateau state with the aim of identifying some of its challenges.  A descriptive survey research design was used for the study. A sample of 71 teachers was drawn from thirty six different secondary schools from three Local Government areas of Plateau State. Three research questions were answered while one hypothesis was formulated and tested at 0.05 level of significance. A multi-stage sampling technique was used to draw out the sample from the population of study. A structured Questionnaire was developed for the purpose of data collection. Data were Analyzed using frequencies distribution and percentages for availability and none availability of equipment. Mean and standard deviation were used for the level of implementation of home economics curriculum while t-test was used to test the hypothesis at 0.05 level of significance. The results revealed that both the old and new Home Economic curriculum was available in many of the schools and was appropriate in terms of goals and content but found weak in its method of implementation; teaching method used in implementing the curriculum was mainly theoretical because there were no adequate laboratories, tools and equipment for proper effective teaching of Home Economics. The studentsâ€™ entrepreneurial competency was suggestively low as there were no substantial production of marketable goods and services as prove of practical knowledge. The study recommended that curriculum developers should reposition home economics curriculum from a predominantly theoretical contents to a more practical orientation for sustainable development. Keyword: Home Economic, Curriculum, Implementation, Private, Public